2017
DOI: 10.1002/ange.201703299
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Tagged Oligonucleotides Coupled with a Magnetic Liquid Support for the Sequence‐Specific Capture of DNA

Abstract: The isolation of specific nucleic acid sequences is am ajor bottlenecki nm olecular diagnostics.M agnetic beads/ particles are typically used as solid supports for the capture of DNAtargets to improve sample throughput but aggregate over time resulting in lower capture efficiency and obstruction of liquid handling devices.H erein, we describe ap article-free approach to sequence-specific DNAe xtraction using am agnetic liquid support and ion-tagged oligonucleotide (ITO) probes.ITO conjugates were synthesized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Another promising application of ILs is nucleic acid extraction and preconcentration; IL-assisted extraction of DNA from aqueous media provides suitable templates for PCR and real-time PCR ( 114–117 ). Sequence-specific extraction of DNA also can be achieved ( 106–108 , 118 , 119 ). A separate, though related branch of studies concerns the application of ILs in targeted analysis of DNA sequences ( 104 ), including detection of mismatched base pairs which can be of use in diagnostics and gene therapy ( 68 ), and electrochemical biosensors for nucleic acids that operate in very small volumes ( 120–129 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another promising application of ILs is nucleic acid extraction and preconcentration; IL-assisted extraction of DNA from aqueous media provides suitable templates for PCR and real-time PCR ( 114–117 ). Sequence-specific extraction of DNA also can be achieved ( 106–108 , 118 , 119 ). A separate, though related branch of studies concerns the application of ILs in targeted analysis of DNA sequences ( 104 ), including detection of mismatched base pairs which can be of use in diagnostics and gene therapy ( 68 ), and electrochemical biosensors for nucleic acids that operate in very small volumes ( 120–129 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, DNase I distributes between the aqueous media and the magnetic IL ( 86 ). Ion-tagged oligonucleotides with magnetic IL supports can be used for sequence-specific capture of DNA, which, in its turn, can be subsequently utilized as a template in PCR and real-time PCR and can be used for transformation of Escherichia coli ( 86 , 106 , 107 ). Similarly, poly-cytosine-tagged nucleotides and cobalt- or nickel-containing trihexyl(tetradecyl)phosphonium ILs can be used ( 108 ).…”
Section: Nucleic Acids In Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Target DNA is then released from the ITO-MIL construct at elevated temperature and subjected to qPCR analysis. The [106] amount of DNA extracted using the MIL-ITO method was ultimately comparable to magnetic beads traditionally used for sequence-specific DNA extractions when applied to aqueous solutions and crude bacterial cell lysate. As shown in Fig.…”
Section: Biological Applications Of Milsmentioning
confidence: 95%
“…The optimized reaction mixture consisting of magnesium chloride, EDTA, ovalbumin, and Tris (pH 8) mitigated PCR inhibition and pH changes caused by hydrolysis of the haloferrate anion. Very recently, Clark et al reported an approach based on a hydrophobic MIL support and ion-tagged oligonucleotides (ITO) that established the first particle-free alternative to magnet-based, targeted DNA extraction [106]. Figure 3A shows a schematic depiction of the MIL-ITO method.…”
Section: Biological Applications Of Milsmentioning
confidence: 99%